1982
DOI: 10.1111/j.1469-8137.1982.tb03393.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIVE PERFORMANCE OF CONIFER POPULATIONS IN VARIOUS TESTS FOR SENSTIVITY TO SO2, AND THE IMPLICATIONS FOR SELECTING TREES FOR PLANTING IN POLLUTED AREAS

Abstract: SUMMARYThe sensitivity of five Pinus and three Picea populations to SOg was compared in various types of fumigation experiment (i) > 9 months at 200 /ig m-^, (ii) 6 h at 8000 /ig m-^, (iii) 9 weeks at 800 fig m », (iv) 12 h (overnight) at 17 000 /xg vcT^ preceded by either 42 days or 6 h at 800 fig m ^ To complement the fumigation experiments the growth of four of the populations was compared at a polluted (London) and a control site (Silwood Park).There was no relationship between the relative sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Concentrations of 1000 ppb for four hours during early summer might be expected to lead to injury, due to the great difference between this concentration and the 7 ppb threshold inferred from field observations. However, Garsed & Rutter (1982) found no relationship between sensitivity to chronic and acute SO.2 fumigations for Scots pine or other conifers. The National Research Council of Canada (1939) found no visible effects on yellow pine Pinus ponderosa with exposures of 1000 ppb for up to 220 h. They found some evidence of a window of greater sensitivity; in one experiment run at the end of March (apparently on newly burst needles), 147 h exposure to 750 ppb SO2 led to extensive foliar necrosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Concentrations of 1000 ppb for four hours during early summer might be expected to lead to injury, due to the great difference between this concentration and the 7 ppb threshold inferred from field observations. However, Garsed & Rutter (1982) found no relationship between sensitivity to chronic and acute SO.2 fumigations for Scots pine or other conifers. The National Research Council of Canada (1939) found no visible effects on yellow pine Pinus ponderosa with exposures of 1000 ppb for up to 220 h. They found some evidence of a window of greater sensitivity; in one experiment run at the end of March (apparently on newly burst needles), 147 h exposure to 750 ppb SO2 led to extensive foliar necrosis.…”
Section: Discussionmentioning
confidence: 79%
“…The National Research Council of Canada (1939) found no visible effects on yellow pine Pinus ponderosa with exposures of 1000 ppb for up to 220 h. They found some evidence of a window of greater sensitivity; in one experiment run at the end of March (apparently on newly burst needles), 147 h exposure to 750 ppb SO2 led to extensive foliar necrosis. Garsed & Rutter (1982) found acute injury on Scots pines fumigated with 2800 ppb SO2 for 6 h or 280 ppb for 9 wk, but not at 70 ppb for 9 months. A factor considered crucial by The National Research Council of Canada (1939) was the humidity during fumigations, with levels below 60% being too low for significant pollutant absorption.…”
Section: Discussionmentioning
confidence: 88%
“…Garsed, Mueller and Rutter (1982) found no effect of 100 pg m" 3 S0 2 on Pinus sylvestris over one year, but on continuing the fumigation for a second year, significant growth reductions took place. This latent effect has recently been confirmed in the field by Garsed and Rutter (1982b), who exposed five conifer species outdoors for two years in the centre of London and at an unpolluted rural site: over the first year all species grew better in London, reflecting higher temperatures in an urban area, but by the end of the second year growth was significantly reduced compared with the rural site. The mean S0 2 concentration in central London throughout the experiment was only 79/igm -3 , although the effect of other pollutants cannot be discounted.…”
Section: Effects On Tree Speciesmentioning
confidence: 76%
“…Olszyk et al (1986) reported that long-term exposure of Yecorra Rojo wheat to air containing 0.15 pL L -l SO2 decreased yields, and that short-term exposure to approximately 1 pL L -t caused acute toxicity effects. Garsed and Rutter (1982) found that the presence of 3 #L L -~ SO2 for 6 hours caused acute damage to several pine (Pinus) species.…”
Section: Time Effects On Phytotoxicity In Cas03 Treated Soilmentioning
confidence: 99%